Uso de tecnologias digitais de informação e comunicação na docência: a formação continuada no Instituto Federal do Acre - IFAC Campus Rio Branco - Paiva, Uthant Benício de (2018)
This dissertation is based on a research of a formative line, with the theme: Use of Digital Technologies of Information and Communication - TDIC in Teaching: Continuing Education at the Federal Institute of Acre - IFAC Campus Rio Branco. It is understood that one of the challenges of the integrated high school teachers of Rio Branco Campus is to insert the Digital Technologies in their pedagogical practices. In this sense, the absence of continuing education is that it would constitute an element that could hamper teaching practice. We also investigate the search and interest of teachers for continuing education in digital technologies within the Rio Branco Campus. The following general objective was defined: to investigate the continuing education of integrated high school teachers through the analysis of the courses offered by the Federal Institute of Acre, Rio Branco Campus, as well as to develop a training course on Digital Information and Communication Technologies for teachers of basic, technical and technological education - EBTT in service, as pedagogical tools for teaching. Having specific objectives: i) to investigate how the continuing education of the teachers of the Federal Institute of Acre, as well as the characteristics of the continuing training of Campus Rio Branco, in the temporal cut of 2015 to 2017; (1998), Tardif (2014), Tardif and Lessard (2014), Nóvoa (1992), Tori (2010) ), Moran (2013), among other authors; iii) diagnose, through a questionnaire, the use of TDIC by the Rio Branco Campus teachers, as well as the ongoing training processes of the participating teachers; iv) construct a proposal of Continuing Teacher Training with the use of TDICs for their educational practice. This is a qualitative research and was held at the IFAC campus in Rio Branco where he selected as subjects of the research teachers of basic education, technical and technological integrated middle school - EMI. The research period lasted from June 2017 to February 2018. During the research, several data collection instruments were used, such as questionnaires (Google Forms), documentary analysis. It was identified from the diagnostic questionnaire the pertinence and the desire on the part of the teachers for continued formation in TDIC. The questionnaire also subsidized the elaboration of a Formative Roadmap on educational tools in Digital Information and Communication Technologies for teaching practice of the technical and technological basic education teachers of the IFAC integrated course. The script is organized in five face-to-face training meetings, constituting the product of this research. This Roadmap can be applied to any group of teachers who wish to improve their educational practices.